Synthesis of poly(allyl 2-ylidene-acetate) and subsequent post-polymerization modification via thiol–ene reaction. Issue 27 (20th June 2016) - Krappitz, Tim; Brauer, Daniel; Theato, Patrick
Abstract : Poly(allyl 2-ylidene-acetate) ( M w = 125 300 g mol −1 ) was synthesized via rhodium mediated catalysis of allyl 2-diazoacetate and its polymerization kinetics and polymer characteristics are presented and discussed. Furthermore, post-polymerization modification utilized the reactive character of poly(allyl 2-ylidene-acetate) by means of thiol–ene reactions. Abstract : Poly(allyl 2-ylidene-acetate) ( M w = 125 300 g mol −1 ) was synthesized via rhodium mediated catalysis of allyl 2-diazoacetate and its polymerization kinetics and polymer characteristics are presented and discussed. This polymer represents the first functional polymethylene accessible by a thiol–ene click-chemistry post-polymerization modification. Thiol–ene reactions were conducted under UV-irradiation utilizing 2, 2-dimethoxy-2-phenylacetophenone as a photo-initiator. Differences to other polymethylenes, such as the inherent ability of poly(allyl 2-ylidene-acetate) to self-crosslink, and polymer characteristics are discussed. The inherent ability to self-crosslink is further utilized to form stable thin films. Subsequent modification of the surface leads to different surface properties as proven by contact angle measurement.